Understanding ICT-based business models in developing countries. (1st September 2004) - Osterwalder, Alexander
It is an essential issue to show how small- and medium-sized enterprises (SMEs) and micro enterprises in developing countries can profit from the opportunities presented through the use of information and communication technologies ICTs. This fosters development and helps narrowing the digital divide. The paper presents a business model framework that helps analysing ICT-based business models and illustrates it through the Village Phone Program of the telecommunication operator Grameen Phone in Bangladesh. Furthermore, the paper proposes a so-called business model handbook to improve knowledge transfer related to ICT-based business models.